Presentation of the Extended Technology Acceptance Model in Sports Organizations - Sardar Mohammadi; Omid Isanejad (The Society of Aging and Physical Activity (SAPA), 2018)
Background. In recent decades, information technology has become a vital component of various aspects of our lives. The use of information technology in different domains has made the analysis of the level of its acceptance/rejection a significant factor in organizations. Objectives. The aim of this study was to illustrate the application of the extended technology acceptance model in sports organizations. Methods. The participants consisted of 350 employees selected from across various Iranian sports organizations. The data were collected according to the perceived ease of use, perceived usefulness, attitude (AT), intention to use (IU), technology self-efficacy (TSE), technology anxiety, perceived enjoyment, and user satisfaction for each variable in the study model. A panel of experts determined the face and content validity of the experiment. The Cranach's alpha coefficient was used to determine the validity. Results. The results showed that AT, self-efficacy, PU, EOU, and user satisfaction have a meaningful effect on the intention to use information technology. The highest effect was related to AT, and the lowest to user satisfaction. Conclusion. It can be claimed that when people have a more positive AT toward the use of information technology, they will exhibit beliefs or excitements, which makes it more viable for them to perceive information technology positively, and consequently increase the intention to use it.